Réponses

2013-04-07T18:21:51+02:00

A=15x+10 +4x+4=19x+14

B=-4x+4x^2+3-3x=4x^2 -7x+3

C=20x-12 - 2x^2+8x-x-4= -2x^2 +27x-20 

 

Pour calculer la valeur de C pour x=-2 tu remplaces dans l'expression C les x par -2 

Meilleure réponse !
2013-04-07T18:27:35+02:00

A = 5(3x + 2) + 4(x + 1 )

A = 15x + 10 + 4x + 4

A = 19x + 14

 

B = (-4x + 3)(1 - x)

B = -4x + 4x² + 3 - 3x

B = 4x² - 7x + 3

 

C = 4(5x - 3) - (2x - 1)(x + 4)

C = 20x - 12 - (2x² + 8x - x - 4)

C = 20x - 12 + 2x² - 8x + x + 4

C = 2x² + 13x - 8

 

2)

Si x = - 2 alors

C = 2*(-2)² + 13*(-2) - 8

C = 2*4 - 26 - 8

C = 8 - 26 - 8

C = - 26